Anthropogenic 236U and 233U in the Baltic Sea: Distributions, source terms, and budgets. (15th February 2022) - Lin, Mu; Qiao, Jixin; Hou, Xiaolin; Steier, Peter; Golser, Robin; Schmidt, Martin; Dellwig, Olaf; Hansson, Martin; Bäck, Örjan; Vartti, Vesa-Pekka; Stedmon, Colin; She, Jun; et al.
Highlights: Source terms of anthropogenic U in the Baltic Sea were identified and quantified. A budget scheme of 236 U in the Baltic Sea was established. Supply, transport, mixing and fate of anthropogenic u were discussed. Pollutant dynamics of the Baltic Sea were investigated. 3D modeling indicates a strong memory effect for pollutants in the Baltic Sea. Abstract: The Baltic Sea receives substantial amounts of hazardous substances and nutrients, which accumulate for decades and persistently impair the Baltic ecosystems. With long half-lives and high solubility, anthropogenic uranium isotopes ( 236 U and 233 U) are ideal tracers to depict the ocean dynamics in the Baltic Sea and the associated impacts on the fates of contaminants. However, their applications in the Baltic Sea are hampered by the inadequate source-term information. This study reports the first three-dimensional distributions of 236 U and 233 U in the Baltic Sea (2018–2019) and the first long-term hindcast simulation for reprocessing-derived 236 U dispersion in the North-Baltic Sea (1971–2018). Using 233 U/ 236 U fingerprints, we distinguish 236 U from the nuclear weapon testing and civil nuclear industries, which have comparable contributions (142 ± 13 and 174 ± 40 g) to the 236 U inventory in modern Baltic seawater. Budget calculations for 236 U inputs since the 1950s indicate that, the major 236 U sources in the Baltic Sea are the atmospheric fallouts (∼1.35 kg) and discharges from nuclear reprocessing plants (> 211 g), and there is a continuous sink of 236 U to the anoxic sediments (589 ± 43 g). Our findings also indicate that the limited water renewal endows the Baltic Sea a strong "memory effect" retaining aged 236 U signals, and the previously unknown 236 U in the Baltic Sea is likely attributed to the retention of the mid-1990s' discharges from the nuclear reprocessing plants. Our preliminary results demonstrate the power of 236 U- 129 I dual-tracer in investigating water-mass mixing and estimating water age in the Baltic Sea, and this work provides fundamental knowledge for future 236 U tracer studies in the Baltic Sea. Graphical abstract: Image, graphical abstract